2020
DOI: 10.1007/s10018-020-00286-3
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of residential water conservation measures in South Africa: the role of water-saving equipment

Abstract: In many urban settings around the world the severity of water scarcity has induced changes in household behavior, leading to reduction in the volume of water demanded. One of the most widely used strategies is the adoption of water-saving equipment that collects, stores and eventually treats wastewater from various sources within the household. This paper investigates the factors that drive adoption of water-saving equipment in Cape Town, South Africa, following the catastrophic "Day Zero" water crisis in 2018… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 96 publications
0
5
0
Order By: Relevance
“…Healthy problems related to water borne diseases were also identified as the reason for households to conserve water. This fact is confirmed by Thiam et al, (2021) when they studied the promotion of residential water conservation measures using latent class analysis and multinomial and conditional logit using a sample of 465 households in South Africa, which found that females were very sensitive to conserving water, stating that they are more vulnerable to diseases in poor hygiene environments as compared to Licensed Under Creative Commons Attribution (CC BY-NC) males. In Rawalpindi, Pakistan, a quantitative study on water conservation attitudes by Iftikhar et al, (2021), applied the theory of reasoned action and planned behaviour to a sample of 399 respondents using reliability analysis and revealed that, with high education, there is a positive relationship between attitudes and behaviour to conserve water resources.…”
Section: Household Participation In Conserving Water Resourcesmentioning
confidence: 77%
“…Healthy problems related to water borne diseases were also identified as the reason for households to conserve water. This fact is confirmed by Thiam et al, (2021) when they studied the promotion of residential water conservation measures using latent class analysis and multinomial and conditional logit using a sample of 465 households in South Africa, which found that females were very sensitive to conserving water, stating that they are more vulnerable to diseases in poor hygiene environments as compared to Licensed Under Creative Commons Attribution (CC BY-NC) males. In Rawalpindi, Pakistan, a quantitative study on water conservation attitudes by Iftikhar et al, (2021), applied the theory of reasoned action and planned behaviour to a sample of 399 respondents using reliability analysis and revealed that, with high education, there is a positive relationship between attitudes and behaviour to conserve water resources.…”
Section: Household Participation In Conserving Water Resourcesmentioning
confidence: 77%
“…in different regions with different economic levels by questionnaire surveys and empirical analysis. The study found that there are four main influencing factors, including attitude characteristics, environmental problems, socio-economic characteristics and attribute characteristics of watersaving products (Millock & Nauges, 2010;Grafton et al, 2011;Thiam et al, 2021). In terms of promotion policies for water-saving products, as early as the 1990s, the Goleta area of California adopted ultra-low-water consumption flush toilets to replace old-style toilets, and distributed 35,000 low-water-consuming showers to the local people for free to prolong the service life of the water supply system (Dunham et al, 1995).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Following the literature, we begin by estimating the utility with the conditional logit model (CLM), which assumes that each ε ij is independently and identically distributed (IID) with Weibull distribution, and consistent with the independence of an irrelevant alternative (IIA) [18,27,58]. The implication here is that the probability of choosing between options is not affected by other alternatives.…”
Section: Theoretical Underpinnings Of the Modelmentioning
confidence: 99%
“…Apart from the CLM and RPL models, latent class analysis (LCA) is another econometric technique that is commonly used in the environmental economics literature to model preferences [27,58]. The advantage of using LCA is that we can recover unobserved classes in the data.…”
Section: Theoretical Underpinnings Of the Modelmentioning
confidence: 99%
See 1 more Smart Citation